(untitled) (KASBIT Business Journal, 2021)
eWOM (Electronic Word of Mouth) or online reviews are frequently read for guidance on purchase. For real and virtual businesses, knowledge of the attributes that make online reviews trustable is of profound importance. This study aims at testing the reviews’ quality, website reputation, and attitude towards the use of reviews as factors affecting eWOM credibility. In turn, how eWOM credibility influences intention to purchase also studies in this research. Responses from 284 young Karachiites are collected through an online questionnaire. Regression, mediation, and moderation analysis are made to test the literature-driven hypotheses. The results revealed that the aforementioned factors could predict 32 percent of the variation in eWOM credibility. Moreover, eWOM credibility influences 34 percent of variations in purchase intentions mediated by eWOM adoption. However, gender is found to have a statistically insignificant effect on these relationships. Results suggest that marketers work on developing a reputation for their websites, which can elevate the level of trust that people place in online reviews and make the review readers more likely to purchase and recommend the product.